2019
DOI: 10.3390/catal9110937
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Catalytic Behavior of Alumina Supported Bimetallic Au-Rh Nanoparticles in the Reduction of NO by CO

Abstract: Alumina-supported bimetallic AuRh catalysts, as well as monometallic reference catalysts, were examined with regard to their structural and catalytic properties in the reduction of NO by CO. Depending on the molar ratio of Au:Rh, the nanoparticles prepared by borohydride co-reduction of corresponding metal salt solutions had a size of 3.5–6.7 nm. The particles consisted of well-dispersed noble metal atoms with some enrichment of Rh in their surface region. NO conversion of AuRh/Al2O3 shifted to lower temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…Despite the significant difference in the BET surface area of the TiO 2 ‐ and KNT‐supported catalysts, the metal particle sizes did not differ much. The energy‐dispersive X‐ray (EDS) line scans presented in Figures 1i and j show that the signals of Au and Rh components overlap with each other, hinting to the formation of AuRh alloy nanoparticles, in line with earlier reported results of similarly prepared AuRh catalysts [24] …”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Despite the significant difference in the BET surface area of the TiO 2 ‐ and KNT‐supported catalysts, the metal particle sizes did not differ much. The energy‐dispersive X‐ray (EDS) line scans presented in Figures 1i and j show that the signals of Au and Rh components overlap with each other, hinting to the formation of AuRh alloy nanoparticles, in line with earlier reported results of similarly prepared AuRh catalysts [24] …”
Section: Resultssupporting
confidence: 87%
“…The addition of metal oxides, such as FeO x [22] and alloying of Au with Pd [23] or Rh, [24] considerably improves the catalytic performance in terms of both activity and selectivity. The catalytic performances of alumina‐supported Au, bimetallic AuRh, and Rh catalysts follows the order of Rh>AuRh>Au [24] . In situ infrared spectroscopic studies demonstrated that CO and NO adsorb on the Au surfaces in different adsorption configurations; on‐top Au 0 −CO, on‐top Au δ+ −CO, bridged CO, Au 0 −NO, Au δ+ −NO, and bridged NO [20,25–27] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations